2020
DOI: 10.1039/c9ra10320a
|View full text |Cite
|
Sign up to set email alerts
|

In vitro toxicity assessment and enhanced drug solubility profile of green deep eutectic solvent derivatives (DESDs) combined with theoretical validation

Abstract: Scheme illustrating the sustainable preparation of deep eutectic solvent derivatives (DESDs), their biological response and water-insoluble hydrophobic drug dissolution trend.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…Various optimized descriptors, such as the highest occupied molecular orbital (HOMO), lowest unoccupied molecular orbital (LUMO), the energy band gap (ΔE = E LUMO − E HOMO ), and the 3Dmolecular electrostatic potential (3D-MEP) surface data, were evaluated for the examined system. 46,47 In addition, the molecular dynamics (MD) of the 150 mM CTAB micelles were measured in an aqueous solution containing 0, 50, and 100 mM PG using Gromacs software package. 48 A spherical aggregate of 100 CTAB monomers was constructed using Packmol software.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Various optimized descriptors, such as the highest occupied molecular orbital (HOMO), lowest unoccupied molecular orbital (LUMO), the energy band gap (ΔE = E LUMO − E HOMO ), and the 3Dmolecular electrostatic potential (3D-MEP) surface data, were evaluated for the examined system. 46,47 In addition, the molecular dynamics (MD) of the 150 mM CTAB micelles were measured in an aqueous solution containing 0, 50, and 100 mM PG using Gromacs software package. 48 A spherical aggregate of 100 CTAB monomers was constructed using Packmol software.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The predicted solubilities reveal an enhancement of 10 4 to 10 5 in [Ch]Cl-lactic acid and alanine-lactic acid, respectively, when compared to the API's aqueous solubility. In agreement with these findings, other [Ch]Cl-based DES have been studied regarding their ability to solubilize lidocaine taking advantage of computational data [52]. The results gathered, based on differences between orbital molecular energies, revealed that high solubility can be obtained by the establishment of hydrogen bonding between the API (NH site) and the chloride anion, as well as between the oxygen atoms of the hydroxyl groups present in the acids and the glycols of HBDs.…”
Section: Des For Apis Solubilizationmentioning
confidence: 71%
“…The predicted solubilities reveal an enhancement of 10 4 to 10 5 in [Ch]Cllactic acid and alanine-lactic acid, respectively, when compared to the API's aqueous solubility. In agreement with these findings, other [Ch]Cl-based DES have been studied regarding their ability to solubilize lidocaine taking advantage of computational data [52]. DES have been widely studied as alternative solvents for the solubility enhancement of anti-inflammatory [46], antipyretic [15], analgesic [47] and antifungal [46] drugs, as well as for the solubilization of nutraceuticals [48][49][50].…”
Section: Des For Apis Solubilizationmentioning
confidence: 93%
“…It was well documented in many liquid state models that the volume, which is not occupied i.e., the unoccupied fraction of the molar volume (V m ) termed as free volume ( f m ), which can be assessed by eqn (10):…”
Section: Arrhenius Equation (Eqn (5))mentioning
confidence: 99%
“…[4][5][6][7][8] Considering this, a large volume of literature has presented the use of DESs in targeted applications viz., pharmaceutical formulations, synthesis of nanomaterials, organic synthesis, catalysis, and gas capture. [9][10][11][12] Apart from ChCl, a particular bend towards betaine hydrochloride (BHC), which is an acidic form of zwitterionic glycine betaine as HBA is observed. Being cheap, biocompatible, and biodegradable BHC with different HBDs is able to form stable DESs at room temperature.…”
Section: Introductionmentioning
confidence: 99%